Z dziejów polonistyki szkolnej okresu niewoli narodowej. Franciszek Próchnicki (1847-1911) = From the History of School Studies of the Polish Language During the Period of National Slavery. Franciszek Próchnicki (1847-1911) - Słowiński, Lech (1922-2005) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Franciszek Próchnicki belongs to the outstanding representatives of grammar school Polish studies during the last quarter of a century after the partition of the country. He was born in 1847 at Brzeżany in Eastern-Galicia, after graduation from the Lvov University in 1873 he became a Secondary-School-teacher, at first at his home town and next at Lvov, where he acted as headmaster of the Secondary School Nr. V from 1891 till to his retirement. Besides that he was an active member of the Higher-School-Teachers'Society, which held the patronage over teachers from popular and Secondary Schools, subsidized the edition of text-books, founded lending libraries for young people, determined on teaching schedules and attached the highest importance to programs for the Polish language.
Keywords: Próchnicki, Franciszek (1847-1911); język polski - nauczanie; Polska - historia - 19 - 20 w.